Catheter-Based Renal Denervation Therapy: Evolution of Evidence and Future Directions. (December 2021) - Kandzari, David E.
Abstract : Motivated by the persistence of uncontrolled blood pressure and its public health impact, the development and evaluation of device-based therapies for hypertension has advanced at an accelerated pace to complement pharmaceutical and lifestyle intervention strategies. Countering widespread interest from early studies, the lack of demonstrable efficacy for renal denervation (RDN) in a large, sham-controlled randomized trial motivated revision of trial design and conduct to account for confounding variables of procedural technique, medication variability, and selection of both patients and end points. Now amidst varied trial design and methods, several sham-controlled, randomized trials have demonstrated clinically meaningful reductions in blood pressure with RDN. With this momentum, additional studies are underway to position RDN as a potential part of standard therapy for the world's leading cause of death and disability. In parallel, further studies will address unresolved issues including durability of blood pressure lowering and reduction in antihypertensive medications, late-term safety, and impact on clinical outcomes. Identifying predictors of treatment effect and surveys of patient-reported outcomes and treatment preferences are also evolving areas of investigation. Aside from confirmatory studies of safety and effectiveness, these additional studies will further inform patient selection, expand experience with RDN in broader populations with hypertension, and provide guidance to how RDN may be incorporated into treatment pathways.